AN ETHNOBOTANICAL STUDY OF MEDICINAL PLANTS USED BY THE TRIBALS - SUJATA BHARTI (International Journal of Multidisciplinary Research and Studies, 2020)
Ethnobotany is the study of the many ways in which various ethnic cultures make use of plants in their day-to-day lives. Dr. John Harsberger of the University of Pennsylvania used the term "ethnobotany" for the first time in 1895 to describe the study of plants used by primitive and aboriginal people. The term was widely accepted and first adopted by J. Walter Fewnes in 1896. Ethnobotany is the study of plants used by primitive and aboriginal people. The field of ethnobotany is subdivided into a large number of disciplines in accordance with the subgroups of the plant kingdom. Some of these subdisciplines include ethnoalgalogy, ethnomycology, ethnobryology, ethnopteridology, and ethnolichenology. Other aspects of botany, such as classification systems, medicinal uses, palaeobotany, and ecology, are referred to as ethnotaxonomy, ethnomedico botany, palaeo (Jain, 1987). Even as far back as prehistoric times, practically all human civilizations have used medicinal plants to cure a variety of human ailments. The sages of India possessed an unrivalled depth of knowledge on the plants used in medicine. The "Rig Veda" is the oldest storehouse of medical knowledge, with its origins dating back to between 4500 and 1600 BC. The "Atharva Veda" came after the "Rig Veda," and it is in this text that a variety of medicinal and spiritual benefits of plants are described. A holistically focused practice or system of health treatment, known as "Ayurvedic medicine," has developed over the years from the traditional Indian medicine that has been practiced for many years and has been very well codified. India is blessed with a diverse environment, ranging from alpine in the Himalayas to tropical wet parts in the south and dry regions in Rajasthan. This range of climates allows India to reap the benefits of each. Due to the existence of such climatic circumstances, the Indian subcontinent is home to a flora that is both diverse and abundant (Rawat and Uniyal, 2003).